2019
DOI: 10.1016/j.jvs.2018.09.060
|View full text |Cite
|
Sign up to set email alerts
|

A multi-institutional analysis of transcarotid artery revascularization compared to carotid endarterectomy

Abstract: Objective: Transcarotid artery revascularization (TCAR) is a novel approach to carotid intervention that uses a direct carotid cut-down approach coupled with cerebral blood flow reversal to minimize embolic potential. The initial positive data with TCAR indicates that it may be an attractive alternative to trans-femoral carotid artery stenting and possibly carotid endarterectomy (CEA) for high-risk patients. The purpose of this study was to present 30-day and 1-year outcomes after treatment by TCAR and to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 22 publications
3
69
0
Order By: Relevance
“…Transcarotid artery revascularization is becoming an accepted alternative to TF-CAS because of its superior stroke and death rates produced in multiple studies. [8][9][10][11][12]20 This study suggests that the procedure has a short learning curve and more importantly, that patients in the early experience are not at risk for inferior outcomes. With increasing experience, operative, flow reversal, and fluoroscopy times, and the use of general anesthesia all decrease.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Transcarotid artery revascularization is becoming an accepted alternative to TF-CAS because of its superior stroke and death rates produced in multiple studies. [8][9][10][11][12]20 This study suggests that the procedure has a short learning curve and more importantly, that patients in the early experience are not at risk for inferior outcomes. With increasing experience, operative, flow reversal, and fluoroscopy times, and the use of general anesthesia all decrease.…”
Section: Discussionmentioning
confidence: 76%
“…Transcarotid artery revascularization (TCAR) has been shown to be an effective alternative to transfemoral carotid artery stenting (TF-CAS). [8][9][10][11][12] The direct surgical access of the common carotid artery paired with highrate carotid blood flow reversal eliminate the inherent risks of TF-CAS. 13 The pivotal and extended access data from the Safety and Efficacy Study for Reverse Flow Used During Carotid Artery Stenting Procedure (ROAD-STER) multicenter trial achieved one of the lowest 30-day stroke rates (1.4%) of any prospective, multicenter carotid artery stenting trial.…”
mentioning
confidence: 99%
“…Recently, trans-carotid artery revascularization (TCAR) has emerged as an alternative to transfemoral CAS (TF-CAS) and CEA, with promising results. 26,27 Therefore, the incorporation of TCAR in the CABG population could be a possible approach as well. Williams et al 28 reported favorable results through a synchronous TCAR-CABG approach for a patient with concomitant severe carotid and CAD, albeit this does not provide robust evidence for the safety of this strategy in CABG population.…”
Section: Discussionmentioning
confidence: 99%
“…A propensity-matched study of TCAR versus CEA demonstrated that TCAR had a similar safety profile to CEA with no significant difference in periprocedural or 1year rates of stroke or death. 82 Taken together, this literature suggests that TCAR may be an effective and safe method for carotid revascularization, though no direct RCT has been performed comparing this new therapy with CEA and CAS.…”
Section: Future Of Carotid Revascularizationmentioning
confidence: 99%